1994
DOI: 10.1152/ajpgi.1994.267.3.g416
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide modulates hepatic vascular tone in normal rat liver

Abstract: This study investigated whether nitric oxide (NO) plays a role in the intrahepatic portal circulation in normal rat livers perfused in situ. N omega-nitro-L-arginine (NNA), a specific NO biosynthesis inhibitor, significantly increased baseline portal pressure compared with controls (P < 0.05). Concentration-effect curves to norepinephrine (NE) were performed. Perfusate flow was maintained as constant, and perfusion pressure was continuously measured. NNA markedly enhanced the responsiveness to NE. This effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
1
9

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 0 publications
4
126
1
9
Order By: Relevance
“…34 Previous studies have shown that NO decreases portal resistance. 35 Our studies confirm that there is some decrease but not normalization of portal pressures with administration of L-arginine the precursor to NO. In the present study, the livers were perfused with blood from donor rats, unlike in the previous study where crystalloids with albumin were used.…”
Section: Discussionsupporting
confidence: 68%
“…34 Previous studies have shown that NO decreases portal resistance. 35 Our studies confirm that there is some decrease but not normalization of portal pressures with administration of L-arginine the precursor to NO. In the present study, the livers were perfused with blood from donor rats, unlike in the previous study where crystalloids with albumin were used.…”
Section: Discussionsupporting
confidence: 68%
“…2,4 This latter component, which results from an insufficient hepatic bioavailability of NO 5,30 and an increased production of circulating and local vasoconstrictors (angiotensin, endothelin, cysteinyl-leukotrienes, thromboxane, and prostaglandins, among others), [31][32][33][34][35] is theoretically amenable to treatment with vasodilators. 36 Attempts to correct the intrahepatic NO deficiency in experimental cirrhosis have involved NOS overexpression by transfecting the liver with adenovirus encoding eNOS, nNOS, or constitutively active AKT 10,37,38 or by selective NO donors.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although it is clear that NO controls basal resistance in the hepatic artery, [18][19][20] a functional role for eNOS in the portal circulation has been more controversial. [21][22][23] By contrast, iNOS is virtually absent in the normal liver but markedly increased in response to inflammation and a variety of oxidative stresses. This led to the postulate that iNOS, but not eNOS, contributed to maintaining sinusoidal perfusion following stress conditions.…”
Section: Blood Flow Regulationmentioning
confidence: 99%